Development of properties of spray flow and nature of pressure distribution in electric arc metalization - Royanov, Vyacheslav; Zakharova, Irina; Lavrova, Elena (Eastern-European Journal of Enterprise Technologies, 2017)
The results of the research on electric arc metallization in the form of a technique and installation, which allow modeling various positions of the electrodes in the spray jet are presented. Direct measurements of the total pressure in the local zone between the ends of the electrodes used for arc metallization are made. The research allows obtaining coatings with refractory oxides, with a large number of alloying elements. These measures will increase their wear resistance. Thus, for 2.4 mm electrodes with a gas pressure at the spraying system inlet of the arc spraying pistol Pinlet=0.5±0.05 MPa and the absence of a gap between the inner parts of the electrode ends in the center of the interelectrode gap, rarefaction is created. The rarefaction value reaches 0.044 MPa. With the gap increase, the degree of pressure drop decreases: when the gap varies from 0 to 1.0 mm, the pressure in the center between the electrode ends varies within 0.044...0.16 MPa. With a gap between the electrode ends of 2 mm or more, the pressure drop is negligible. The characteristic changes in the spray jet structure in the presence of electrodes are confirmed by the results of shadow photography. The results obtained allowed making adjustments to the process flow diagram of electric arc metallization, with the specification of the presence of the zone of air flow around the electrodes and pressure drop in the interelectrode gap. Optimum conditions for the arc functioning are achieved with such a ratio of the rates of feeding and melting of the electrodes, when the gap between the inner surfaces of the ends is within 0.5...1.0 mm. The proposed technology will allow restoring the working surfaces of parts of machines and mechanisms in mechanical engineering, agriculture, car building